The human brain arterial circle variants and integrated classification of individual-typological variability - V. N. Nikolenko; A. V. Pavlov; V. E. Timofeev; S. R. Zherebyatyeva; S. M. Timofeeva (Сеченовский вестник, 2018)
Objective. The variability of the design of the arterial circle of the human brain (ACHB) has been studied.Materials and methods. The systematization was carried out and the original classiﬁcation of the variants of ACHB was compiled. The study was performed on 116 brain preparations of adult people (64 men and 52 women). The causes of death of these people were not associated with diseases or trauma of the brain. Dissection of the vessels ACHB and central arteries was carried out after the injection of contrasting arteries mixture (mascara - gelatin).Results. There are two types of ACHB design, including two subtypes (4 in total). First of all, the variants of the individual-typological variability (VITV) of the circle design were combined depending on the presence or absence of the sign of its closure in the types of construction of the ACHB - closed or open. The type of construction is one of the integral and basic principles of classiﬁcation. It serves as a criterion for the morphofunctional consistency of the ACHB. The second level of systematization of the VITV structure of ACHB is associated with the allocation in types of two subtypes in each of them. This is based on the presence or absence of symmetry of the ACHB form. This sublevel is a systemic - all variants of AKBM are caused by the presence or absence, or the degree of development (from hypoplasia to hyperplasia) of the arteries forming it. In accordance with the selected types and subtypes of the ACHB, the identiﬁed VITV circle was classiﬁed.Conclusions. The statistically signiﬁcant prevalence of closed and asymmetric ACHB among both men and women has been established. The proposed integral classiﬁcation is based on the basic morphogeometric characteristics of the ACHB. It takes into account the anatomy of both individual arteries and the circle as a whole, without dividing it into the front and back sections and treating the arterial circle as a single entity.